RURAL WOMEN AND ENTREPRENEURSHIP - Jovana Čikić; Marica Petrović; Živojin Petrović (Ekonomika Poljoprivrede (1979), 2011)
Confronted with the continual decline of social vitality, contemporary Serbian rural areas are on search for the development chances. On the quest for the rural renewal strategy, possibilities for development of rural entrepreneurship are being analyzed. In addition, the role of rural women in this process is examined because rural entrepreneurship is considered as a chance to improve their social position, but also a mechanism for improvement of the quality of life within the local rural community.